Perancangan dan Implementasi Front end Website Profile & Crud Product Knowledge di PT. Panca Utama - Nancy Vanessa; Hendi Sama; Mangapul Siahaan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2025)
Digital transformation is a key requirement for companies that want to compete in the modern era, including for PT. Panca Utama, a hospitality equipment provider company that has been operating for more than two decades. In order to increase digital visibility and expand marketing reach, a community service activity was carried out in the form of designing and implementing a company website that includes a company profile and CRUD features for managing product information. The project was implemented using the Scrum methodology and involved the development of a user interface (front-end) using HTML, CSS, and JavaScript, as well as a Django-based backend. The final result is an official website that is informative, interactive, and easily accessible has been successfully implemented, enabling the company to appear more professional and efficient in serving customers and supporting future business growth.